2004
DOI: 10.1002/ange.200300616
|View full text |Cite
|
Sign up to set email alerts
|

Katalytische Markownikow‐ und Anti‐Markownikow‐Funktionalisierung von Alkenen und Alkinen

Abstract: Reaktionen zur selektiven Veredelung von Alkenen zählen zu den wichtigsten Methoden in der Organischen Synthese. Durch die Entwicklung von Übergangsmetallkatalysatoren in den letzten Jahrzehnten können heute alle Arten von Selektivität bei einer Vielzahl von Transformationen effizient gesteuert werden. Auch 100 Jahre nach dem Tod von Vladimir Markownikow – dem Pionier auf diesem Gebiet – ist die regioselektive Funktionalisierung von Alkenen und Alkinen immer noch ein wichtiges Forschungsziel: Besonders die Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
65
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 274 publications
(72 citation statements)
references
References 318 publications
0
65
0
6
Order By: Relevance
“…[3,4] Ruthenium catalysts are known to activate alkynes towards nucleophilic attack by coordination of the triple bond to the electrophilic metal center. [5,6] Depending on the tautomerizationb etween h 2 -alkyne and vinylidene binding modes the ruthenium complexesp romote either the Markovnikov addition or affordt he anti-Markovnikovp roducts by nucleophilic attack at the a-carbon of the vinylidenea nalogues (Scheme 1). [7][8][9] Then ucleophilic addition of carboxylic acids to terminal alkynes is an elegant method to produce enol esters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] Ruthenium catalysts are known to activate alkynes towards nucleophilic attack by coordination of the triple bond to the electrophilic metal center. [5,6] Depending on the tautomerizationb etween h 2 -alkyne and vinylidene binding modes the ruthenium complexesp romote either the Markovnikov addition or affordt he anti-Markovnikovp roducts by nucleophilic attack at the a-carbon of the vinylidenea nalogues (Scheme 1). [7][8][9] Then ucleophilic addition of carboxylic acids to terminal alkynes is an elegant method to produce enol esters.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] Thef irst catalytic system which was able to generate b-oxo estersw as described by Mitsudo andW atanabe. [30] They employed am ixture composed of bis(h 5 -cyclooctadienyl)ruthenium, P(n-Bu) 3 [11,[27][28][29]31,32] In addition, Cadierno and co-workers have shown that ruthenium(II) complexes containingh ydrosoluble phosphine ligands enable the formation of b-oxo estersi na queous medium. [27] Recently,w ec ould show for the first time that mononuclear ruthenium compoundso ft he type [Ru(CO) 2 (PPh 3 ) 2 (O 2 CR) 2 ]( R= CH 2 OCH 3 , i-Pr, t-Bu, 2-cyclo-C 4 H 3 O, Ph) are efficientc atalysts for the addition of carboxylic acids to propargylic alcohols,e ven when challengings ubstrates were applied.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Catalytic enantioselective intermolecular hydroamination is a highly attractive, atom economical approach for the synthesis of non-racemic amines and their derivatives, and has been the subject of much attention. [4] Despite extensive effort, efficient methods for catalytic enantioselective intermolecular hydroamination are rare. [5] Although the enantioselective intermolecular hydroamination of allenes would be an efficient method for the synthesis of a-chiral allylic amines, [6,7] only one example has been reported, which requires internal allenes, has a limited scope, and provides only moderate levels of enantioselectivity (Scheme 1 a).…”
mentioning
confidence: 99%
“…(2)] fashion. [2,3] Therefore, from an industrial point of view this reaction could be a highly useful and efficient method for the synthesis of a wide variety of industrially relevant basic and fine chemicals, as well as pharmaceuticals, from readily available and inexpensive starting materials.…”
Section: Introductionmentioning
confidence: 99%